2014
DOI: 10.1016/j.psychres.2014.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Who stays, who benefits? Predicting dropout and change in cognitive behaviour therapy for psychosis

Abstract: Who stays, who benefits? Predicting dropout and change in cognitive behaviour therapy for psychosis, Psychiatry Research, http://dx.doi.org/10.1016/j. psychres. 2014.02.012 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 43 publications
3
38
1
6
Order By: Relevance
“…Studying interpersonal elements of treatment, Lincoln et al 37 reported that lack of insight predicted drop out from cognitive behavior therapy in patients with psychosis. Poor insight was linked to poorer therapeutic alliance with a prescribing psychiatrist in schizophrenia and bipolar disorder.…”
Section: Clinical Insight Is Associated With Therapeutic Alliancementioning
confidence: 99%
“…Studying interpersonal elements of treatment, Lincoln et al 37 reported that lack of insight predicted drop out from cognitive behavior therapy in patients with psychosis. Poor insight was linked to poorer therapeutic alliance with a prescribing psychiatrist in schizophrenia and bipolar disorder.…”
Section: Clinical Insight Is Associated With Therapeutic Alliancementioning
confidence: 99%
“…Perivoliotis et al () examined CBTp dropout in a psychosis sample and found that higher levels of delusions at baseline—but not voices or insight—predicted a failure to move past the assessment phase, but none of these variables predicted dropout once therapy had commenced. Lincoln and colleagues () conducted a similar study and found that the strongest dropout predictors were a lack of insight and low social functioning (but not baseline symptom severity, comorbidity, neurocognitive defects, or reasoning biases).…”
Section: Introductionmentioning
confidence: 99%
“…Although the above-mentioned observed effects of the group psychotherapeutic programme seem to be promising, these programmes are feasible only for a limited proportion of patients with schizophrenia and therapists have to deal with significant dropouts (Lincoln et al, 2014;Simhandl & K€ onig, 2011). In this context, insufficient effort has as yet been devoted to research into which personal variables at a baseline of treatment would predict completion of the psychotherapeutic programme and which patients could better benefit from the programme.…”
mentioning
confidence: 99%
“…In this context, insufficient effort has as yet been devoted to research into which personal variables at a baseline of treatment would predict completion of the psychotherapeutic programme and which patients could better benefit from the programme. For example, certain specific variables may play a role, such as being married (Kami nski & Lisiecka, 2002), female sex (Priebe et al, 2011), low number of previous hospitalizations (Mintz, O'Brien, & Luborsky, 1976), or shorter duration of the illness (Lincoln et al, 2014), which were found as good predictors. Also paid work was revealed as a good predictor of clinical improvement in several studies (Bond et al, 2001;Bryson, Lysaker, & Bell, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation